Stock market volatility changes in Europe: 1989-2014 - Menezes, R.; Oliveira, Á. (ISF 2014 - The 34th International Symposium on Forecasting, 2014)
In this paper we analyze the behavior of stock market volatility between 1989 and 2014 using daily data. Since volatility can be seen as a risk measure in the market, we seek for structural breaks and regime shifts over the period, in particular between 2007 and 2010. We also seek for causality effects between long-run interest rates and stock market returns. Asymmetric information is also accounted for as well as changes in persistency before and after the recent succession of crises. Finally, we perform out-of-sample tests for assessing the forecasting capability of our models and how the crises affect such capabilities. The analysis is performed using daily data from a significant number of European countries including Eurozone and non- Eurozone countries. It is clear that the sovereign debt crises in Greece, Ireland and Portugal played an important role and quantifying these effects is an important task. Altogether, persistency increased dramatically from before to after the 2008 crisis across all Europe which may be an indicator that the European crisis is not yet completely controlled but also not out-of-control.